“The very land of romance”: Original Compositions on Spain and the Spanish in The Southern Literary Messenger (1834-1864) - José Manuel Correoso-Rodenas (European Journal of American Studies)
It is undeniable that Spain and the culturally Spanish has had a strong influence in the shaping of US American identity and culture. From the notions of Jeffersonian Quixotism to the buildings of Rafael Guastavino populating New York, the presence of Spain has been a constant. If we take into consideration the South as a region, this influence is even stronger. Not only historical ties (Hernando de Soto, Spanish Texas and Florida…) but also cultural addenda, like the Carlist participation in the Confederate army, arise. In this sense, it is not strange that The Southern Literary Messenger, one of the most relevant publications of the South as a region and of the United States as a whole, devoted many of its articles to the spread and discussion of topics related to the Iberian country. The aim of this article is to expose how this particular stream of influence was constructed, and which were the aspects preferred by authors and editors in order to highlight Spain. As seen below, concepts such as honor or the so-called Black Legend will be (could not be otherwise) present; however, along with them, other less widely discussed issues will appear, such as the essence of the Canary Islands, or the tragedy of Rafael del Riego, just to mention a few examples.